Revealing Rebellion in Abiayala : The Insurgent Poetics of Contemporary Indigenous Literature - Burdette, Hannah (Book collections on Project MUSE., 2019)
"A masterful study of the intersection between Indigenous literature and social movements in the Americas"--Provided by publisher